Effects of Microencapsulated Phase Change Material on the Behavior of Silty Soil Subjected to Freeze-Thaw Cycles - Gencdal, Hazal Berrak; Kilic, Havvanur (MDPI, 2023)
Freeze-thaw (F-T) cycles are one of the most important factors affecting the performance of silty soils with high kaolin content in seasonally freezing regions. This study investigates the improvement of a high-plasticity clayey silt soil (MH) with microencapsulated phase change material (mPCM) to prevent changes in mechanical properties when subjected to freeze-thaw cycles. Unconfined compression, one-dimensional compression, and freeze and thaw tests were performed to evaluate the behavior of treated soil under different freeze/thaw cycles and with different mPCM ratios. It has been observed that the mPCM additive decreased the unconfined compression strength (UCS); however, the strength of the soil held constant during the increasing F-T cycles, and the increase in the mPCM additive content increased the strength of the soil. The inclusion of mPCM affected the compression of the soil and increased settlement ( increment H), although the settlement remained constant with increasing freeze-thaw cycles. It has been noted that the compression behavior, which is least affected by the unconfined compressive strength and freeze/thaw cycles, is achieved with the addition of 10% mPCM. As a result of the tests, it was determined that the most suitable additive mPCM ratio is 10% for the compression and strength behaviors.
Keywords: microencapsulated phase change material; unconfined compressive strength; one-dimensional compression; freeze-thaw cycle; volume change behavior; high-plasticity silt; HYDRAULIC CONDUCTIVITY; POTENTIAL APPLICATIONS; STABILIZATION; PERFORMANCE; CONCRETE; CLAY; Science & Technology - Other Topics; Environmental Sciences & Ecology